GLOBALIZERS TENDENCIES OF RELIGIOUS INTEGRALISM TO CIVILIZATIONS (Religious dialogue and cooperation, 2025)
This year’s paper for the Conference on “Religion and Globalization” has the theme: religionas a globalizer. The subject of the research is narrowed to the Problematic Question: How dointegrist and integralist elements in major world religions stimulate globalization processes, andhow is the globalization of national cultures into large civilizational wholes implemented throughreligious-integralist tendencies? The aim of the research is to point out the strong connection betweenreligious integrism, cultural-political integralism and the globalization of national culturesinto unique spiritual civilizations. The methods that will be used in the research are: observationmethod, cross-cultural method, comparative approach, content analysis... Practical contributions:in the area of interreligious tolerance, interfaith cooperation and intercultural dialogue. Scientificcontribution: understanding the significance of the social background of religious integralism,researching the globalization of local and national cultures, deepening cognitive insights into therelationship: religion → culture → globalization. Social significance, primarily, in the advancementof scientific disciplines: sociology of religion, civilization studies and cultural studies.
Keywords: religious integrism/integralism; civilizations; culture; globalization; interreligious cooperation